The Influence of Earnings Management, Audit Quality and CEO Duality on Tax Avoidance - Darwin Marasi Purba (STIE Binaniaga, 2018)
This study aims to get the empirical evidence about the influence of earnings management, audit quality and CEO duality on the tax avoidance. Tax avoidance has used an effective tax rate (ETR) by calculating the corporate taxes expenses divided by the earnings before income and tax during a certain period. Population of this research are the manufacturing companies in Indonesia Stock Exchange in 2014-2016 which 48 companies are using the purposive sampling technique. Methods of data analysis has applied the descriptive statistical analysis and multiple linear regression. These results have indicated that earnings management, audit quality and CEO duality have had a significant effect simultaneously on the tax avoidance. However, partial test results have shown that the audit quality and CEO duality have not affected the tax avoidance. While the earnings manegement has had a significant effect on the tax avoidance.Keyword: effective tax rate, earnings management, tax avoidance.